Islamic worldview on cosmology - Hassan @ Mohamed, Nor Jana (IIUM Press, 2025)
Cosmology is a branch of metaphysics that deals with the nature of the universe, and the cosmos or multiverses. It is a narrative that describes the natural order of the universe, as well as a branch of astronomy that deals with the origin, structure, and space-time relationships of the universe. This chapter will discuss the necessary premises or philosophical foundations of the study and understanding of the Cosmos from the Worldview of Islam, which includes, but not confined to the following concepts of Qadar of Allah, Sunnatu’Llāh, and Tashkīr.